Crossover from single-file to fickian diffusion in carbon nanotubes and nanotube bundles: pure components and mixtures - Liu, Ying-Chun; Moore, Joshua D.; Chen, Qu; Roussel, Thomas J.; Wang, Qi; Gubbins, Keith E. (Diffusion Fundamentals, 2009)
The diffusion mechanism of pure component Ar and binary mixtures of Ar/Kr and Ar/Ne confined in single-walled carbon nanotubes (SWNTs) and bundles was investigated by a combined Grand Canonical Monte Carlo and molecular dynamics study. For Ar confined in SWNTs, a crossover from single-file to Fickian diffusion existed when the density of Ar was a minimum as a function of the SWNT diameter. Argon diffused by a single-file mechanism in SWNTs smaller than an accessible diameter of 1.76σAr, corresponding to (7,7), (12,0) and (8,6) SWNTs but by a Fickian mechanism for SWNTs larger in diameter. Both components in Ar/Kr mixtures had a single-file diffusional mechanism in (6,6) and (7,7) SWNTs and a Fickain mechanism for SWNTs larger in diameter. Likewise, both components in a Ar/Ne mixtures had a single-file diffusional mechanism in a (6,6) CNT, and Ar had a single-file diffusional mechanism in a (7,7) SWCNT. However, Ne in the Ar/Ne mixture exhibited Fickian diffusion in the (7,7) SWNT , which indicated bi-modal diffusion. Larger diameters of SWNTs provided Fickian diffusion for both components in an Ar/Ne mixture. Argon diffused in a (25,0) SWNT bundle (with a bimodal pore size distribution) in a bimodal mechanism, with Ar diffusing in single-file in interstitial sites and in a Fickian mechanism in inner nanotube channels. In all cases of single-file diffusion the mean-squared displacement (MSD) of the fluid molecules had a square root of time dependence, while molecules diffusing by a Fickian mechanism had a MSD with a linear time dependence.